Pest characteristics of Trigonorhinus sp. (Coleoptera: Anthribidae) and the developmental process of its galls in Caragana liouana Zhao Y. Chang and Yakovlev. (5th April 2023) - Zhang, Yanru; Hu, Yaru; Jiang, Haiyan; Zhao, Shengguo; Lei, Jingwen; Wang, Ruigang; Chen, Yuhong
Abstract: In recent years, a Trigonorhinus sp. (Coleoptera) has caused serious damage to Caragana liouana Zhao Y. Chang and Yakovlev, a major ecological restoration shrub in China. Here, we survey the occurrence and damage pattern of Trigonorhinus sp. and its galls and compare the growth of affected and unaffected plants. Trigonorhinus sp. larvae usually infest the main trunk and lateral branches of the plant, causing the affected branches to become partially swollen and verrucose. Galls develop in stages depending on whether eggs are laid in May or July and proceed in sequence over three years from egg-laying to formation, expansion, dormancy, maturity, dormancy, maturity, and death. Galls inhibit plant development to some extent. On average, six (at least one, and no more than 18; standard error of the mean = 3) larvae occupy each gall, and the number of larvae within a gall did not significantly affect gall size. Gall size significantly affected branch dieback, and large-diameter infested branches had larger galls. This study clarifies the growth dynamics of Trigonorhinus sp. galls and provides a basis for further research into the growth mechanism of the species' galls.